Adenosinergic Signaling as a Key Modulator of the Glioma Microenvironment and Reactive Astrocytes - Debom, Gabriela N.; Rubenich, Dominique S.; Braganhol, Elizandra (Frontiers in Neuroscience, 2022)
Astrocytes are numerous glial cells of the central nervous system (CNS) and play important roles in brain homeostasis. These cells can directly communicate with neurons by releasing gliotransmitters, such as ATP and glutamate, into the multipartite synapse. Moreover, astrocytes respond to tissue injury in the CNS environment. Recently, astrocytic heterogeneity and plasticity have been discussed by several authors, with studies proposing a spectrum of astrocytic activation characterized by A1/neurotoxic and A2/neuroprotective polarization extremes. The fundamental roles of astrocytes in communicating with other cells and sustaining homeostasis are regulated by purinergic signaling. In the CNS environment, the gliotransmitter ATP acts cooperatively with other glial signaling molecules, such as cytokines, which may impact CNS functions by facilitating/inhibiting neurotransmitter release. Adenosine (ADO), the main product of extracellular ATP metabolism, is an important homeostatic modulator and acts as a neuromodulator in synaptic transmission via P1 receptor sensitization. Furthermore, purinergic signaling is a key factor in the tumor microenvironment (TME), as damaged cells release ATP, leading to ADO accumulation in the TME through the ectonucleotidase cascade. Indeed, the enzyme CD73, which converts AMP to ADO, is overexpressed in glioblastoma cells; this upregulation is associated with tumor aggressiveness. Because of the crucial activity of CD73 in these cells, extracellular ADO accumulation in the TME contributes to sustaining glioblastoma immune escape while promoting A2-like activation. The present review describes the importance of ADO in modulating astrocyte polarization and simultaneously promoting tumor growth. We also discuss whether targeting of CD73 to block ADO production can be used as an alternative cancer therapy.